2002
DOI: 10.1080/13678860210143550
|View full text |Cite
|
Sign up to set email alerts
|

Organizational learning and resistance to change in Estonian companies

Abstract: Background: Cognitive Muscular TherapyTM (CMT) is an integrated behavioural intervention developed for knee osteoarthritis. CMT teaches patients to reconceptualise the condition, integrates muscle biofeedback and aims to reduce muscle overactivity, both in response to pain and during daily activities. This nested qualitative study explored patient and physiotherapist perspectives and experiences of CMT.Methods: Five physiotherapists were trained to follow a well-defined protocol and then delivered CMT to at le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
47
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(49 citation statements)
references
References 1 publication
0
47
0
1
Order By: Relevance
“…There are several advanced studies has been conducted in resistance to change, however there are lack of studies investigated resistance to change due two demographics variable"s only little studies which concern only with the relationship between employee age and resistance to change like Alas and Sharifi (2002) concluded that 59% of young managers supported change from the onset and 52% of the old managers started to give maximum support after realizing the benefits of change. Galangar (2004) concluded that there is a positive correlation between age and resistance to organizational change.…”
Section: Researcher Comments On Previous Studiesmentioning
confidence: 99%
“…There are several advanced studies has been conducted in resistance to change, however there are lack of studies investigated resistance to change due two demographics variable"s only little studies which concern only with the relationship between employee age and resistance to change like Alas and Sharifi (2002) concluded that 59% of young managers supported change from the onset and 52% of the old managers started to give maximum support after realizing the benefits of change. Galangar (2004) concluded that there is a positive correlation between age and resistance to organizational change.…”
Section: Researcher Comments On Previous Studiesmentioning
confidence: 99%
“…Here the ability to learn using a trial and error method by making mistakes and learning from these mistakes plays an important role. Managerial support for personal development and training is also significant [38].…”
Section: Questionnaire For Measuring Organizational Learningmentioning
confidence: 99%
“…On the one hand, employees should be aware of and committed to the business objectives and the process of change. And on the other hand, they should also be encouraged to take initiative and be active in relation to their own work [38].…”
Section: Questionnaire For Measuring Organizational Learningmentioning
confidence: 99%
See 2 more Smart Citations